PENGARUH PENGGUNAAN BUKU BAGAN MANAJEMEN TERPADU BALITA SAKIT (MTBS) TERHADAP PENINGKATAN PENGETAHUAN PETUGAS DI PUSKESMAS BELIMBING KOTA PADANG TAHUN 2018 - Tisnawati, Rischa Hamdanesti, Zulferi (Menara Ilmu, 2018)
The research aims to know the effect of the use of IMCI chart book to the increase of thestaff in the Community Health Clinic of Belimbing in 2018. The type of the research usesanalytic using pre-experimental design and One Group Pretest-Posttest Design approach.Processed January 29 until February 5 in 2018. The population of the research is all staffin Community Health Clinic of Belimbing in 2018 with the total 45 people and 18 peoplefor sample using purposive sampling technique. Tools of the research are questionnaire.The writer uses a univariate data analysis to know the average of knowledge increasebefore and after treatment, bivariate analysis using non parametric test statistic of MannWhitney test with Convidence Interval which its value is 95% (95% 05). The result of thisresearch is the effect of training on the use of IMCI chart book to increase the knowledgeof staff before and after being given treatment at Community Health Clinic of Belimbing inPadang in 2018 with p value = 0,028.The use of IMCI chart book influences thenowledge of the staff. It is expected to- arrange the management of local goverment clinicof Belimbing related to the facilities and infrastructures an review the tasks which wereassigned to the staff, also prepare the training uses effective methods seen from its timeand budget. It is important to have coordination with Health office to conduct the facilitiesof IMCI so that the IMCI service implementation could be better.Keywords : The Use of IMCI Chart Book, Knowledge